Predation has no competition: factors influencing space and resource use by echinoids in deep‐sea coral habitats, as evidenced by continuous video transects. (17th December 2014) - Stevenson, Angela; Mitchell, Fraser J. G.; Davies, Jaime S.
Abstract: Predation and competition are highly influential factors determining space use in foraging animals, and ultimately contribute to the spatial heterogeneity observed within habitats. Here we investigated the influence of competition and predation on space and resource use via continuous video transect observations – a tool that has not previously been employed for this purpose. This study therefore also evaluates video data as a pragmatic tool to study community interactions in the deep sea. Observations were compiled from 15 video transects spanning five submarine canyons in the Bay of Biscay, France. Substrate choice, positioning on the coral, echinoid aggregate size, and the presence/absence of predators ( e.g . fish and decapods) as well as competitors (both inter‐ and intra‐specific) were recorded. Two dominant co‐existing echinoid taxa, echinothurids and Cidaris cidaris (3188 total observations), were observed in the study. For the echinothurids, no significant trends were detected in the inter‐ and intra‐specific competition data. For Cidaris cidaris, significant shifts in substrate use were correlated to the presence of inter‐specific competitors (echinothurids), whereby an increase in dead coral substrate usage was observed. Highly significant patterns were detected amongst echinoids near fish and decapod predators. A shift to the base of the coral infra‐structure was correlated to the presence of fish, and fewer individuals were observed in the open areas of the reef and a greater number were found in the mid and top sections of the coral when in the presence of decapods. Aggregates formed irrespective of the presence of predators. Aggregations are likely to form for feeding and reproduction rather than for defensive purposes; and migration along the coral infra‐structure may be a predator‐driven behaviour as echinoids seek refuge from predators. Predation risk might play a stronger – or more detectable – role in structuring echinoid space and resource use in deep‐sea coral habitats. In addition, the study successfully detected patterns in the video data thereby demonstrating its potential usefulness for similar ecological studies on other deep‐dwelling megabenthos.